2018
DOI: 10.3847/1538-4357/aaa12a
|View full text |Cite|
|
Sign up to set email alerts
|

A Detailed Observational Analysis of V1324 Sco, the Most Gamma-Ray-luminous Classical Nova to Date

Abstract: It has recently been discovered that some, if not all, classical novae emit GeV gamma-rays during outburst, but the mechanisms involved in the production ofgamma-rays are still not well understood. We present here a comprehensive multiwavelength data set-from radio to X-rays-for the most gamma-ray-luminous classical nova to date, V1324 Sco. Using this data set, we show that V1324 Sco is a canonical dusty Fe II-type nova, with a maximum ejecta velocity of 2600 km s −1 and an ejecta mass of a few´-10 5  M . The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 110 publications
(232 reference statements)
5
36
0
Order By: Relevance
“…The same spectroscopic signature was observed in the recent dust forming CO nova V1324 Sco (Finzell et al 2018). Although the line profiles presented in that paper cover only the period before the main event, that part of the expansion when the ejecta transitioned to optically thin in the Fe-curtain, one Balmer line profile taken 800 days after the deep minimum shows precisely the same signature as we have shown here for late spectra.…”
Section: Dust Signatures In Other Novaesupporting
confidence: 83%
“…The same spectroscopic signature was observed in the recent dust forming CO nova V1324 Sco (Finzell et al 2018). Although the line profiles presented in that paper cover only the period before the main event, that part of the expansion when the ejecta transitioned to optically thin in the Fe-curtain, one Balmer line profile taken 800 days after the deep minimum shows precisely the same signature as we have shown here for late spectra.…”
Section: Dust Signatures In Other Novaesupporting
confidence: 83%
“…The equatorial wind ejecta is opaque in the continuum at this phase leading to spectra that, despite the somewhat unusual geometry, could well appear consistent with the usual optically-thick early stage of the nova outburst. L2 spiral shocks powering early-time optical emission from novae would be consistent with observations of periodicities at the orbital period in the early-time light curves of some novae [30][31][32] .…”
supporting
confidence: 85%
“…We adopted the linear MMRD distance of d = 4.2 kpc as a reference distance in our analysis but caution that the uncertainties in the distance do not include systematic uncertainties in the MMRD. For example, Kasliwal et al 32 found that some novae with t 2 ∼ 10 days (the observed value for ASASSN-16ma) were up to 2 mag fainter than predicted by the MMRD, which would imply a distance of only 1.7 kpc. At this short distance the inferred luminosity could be consistent with the Eddington luminosity, depending on the mass of the white dwarf.…”
mentioning
confidence: 93%
“…Another source studied by Rupen's team, V1723 Aql, showed an unexpectedly rapid turn-on in the radio, an anomalous spectral index (α ∝ ν 1.3 ), a double-peaked radio light curve, and T B > 10 6 K (Weston et al 2016b). A double-peaked radio light curve was also seen in V1324 Sco (Finzell et al 2018).…”
Section: Cataclysmic Variables (Cvs)mentioning
confidence: 76%